Facile sol-gel synthesis and enhanced photocatalytic activity of the V2O5-ZnO nanoflakes - Shukla, Prakhar (H. : ĐHQGHN, 2019)
The structural, optical and photocatalytic properties of V2O5-ZnO nanoflakes are reported. A facile sol-gel method was employed for the synthesis of ZnO and V2O5-ZnO nanostructures. Structural characterizations revealed a flake-type structure of V2O5-ZnO obtained from ZnO nanorods. A decrease in the band gap from 3.28 eV for ZnO to 2.64 eV for V2O5-ZnO was observed by Ultraviolet (UV)-Visible spectroscopy. The V2O5-ZnO based photodegradation of methylene blue (MB) dye indicated that the anchoring of V2O5 in the ZnO composite improved the photocatalytic efficiency of the composite under irradiation of the visible light